Corrigendum to "Development of SARS-CoV-2 Inhibitors Using Molecular Docking Study with Different Coronavirus Spike Protein and ACE2” [J Mol Docking. 2021;1(2):1-14] - Israa Mohamed Shamkh; Dina Pratiwi; Hanaa S. Omar (Journal of Molecular Docking, 2021)
Authors have found an error in the previous version (Shamkh, IM, & Pratiwi, D. (2021). Development of SARS-CoV-2 Inhibitors Using Molecular Docking Study with Different Coronavirus Spike Protein and ACE2. Journal of Molecular Docking, 1(1), 1-14. https://doi.org/10.33084/jmd.v1i1.2212), of which Dr. Hanaa S. Omar as supervisor of the research, is not listed as one of the authors. In this note, Dr. Hanaa S. Omar was added as one of the authors, with the status of the corresponding author in the study.